Pelatihan Pramusaji Kale Tortilla Eldorado The Family Club Bandung - Riyadi, Heru; Sundayana, Dendy (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2017)
Human resources is one of the important assets of the company, though the presence of the high-tech equipment that is human resources which will operate. Therefore the interest of the company to maintain the performance of its employees, as management's assessment of the company. In creating a good performance, it is necessary to factor that can create the best performance. Training is a factor that can improve employee performance. Indication of the low performance of employees in Cafe the Family Club Eldorado Tortilla Bandung allegedly due to lack of effective implementation of the training program at the hotel. The low performance is caused by the waitress several factors which include lack of training implementation.Implementation of training greatly affect the performance of the waitress, this is evidenced by the results of the analysis are correlated between the effect of the training on the performance that is equal to 0.869 in the strong range. And the coefficient of determination of 71.4%, meaning that 71.4% of performance is determined by training. While 28.6% influenced by factors - other factors.In addressing this issue, needs to be improved with the implemented training to employees.